2013
DOI: 10.7314/apjcp.2013.14.11.6949
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of β-Cyclodextrin-Helenalin Complexes on H-TERT Gene Expression in the T47D Breast Cancer Cell Line - Results of Real Time Quantitative PCR

Abstract: Background: Nowadays, the encapsulation of cytotoxic chemotherapeutic agents is attracting interest as a method for drug delivery. We hypothesized that the efficiency of helenalin might be maximized by encapsulation in β-cyclodextrin nanoparticles. Helenalin, with a hydrophobic structure obtained from flowers of Arnica chamissonis and Arnica Montana, has anti-cancer and anti-inflammatory activity but low water solubility and bioavailability. β-Cyclodextrin (β-CD) is a cyclic oligosaccharide comprising seven D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 20 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…While Chemotherapy has toxic side effects in healthy tissues in treatment of human cancers, Nanotechnology attempts to resolve these problems by encapsulating or loading drugs to nonmaterial which are resistant to drug efflux (Tsuda, 2010;Ghasemali et al, 2013). In recent times, Cyclodextrin nanoparticles are used mostly as recyclable transporters for drug delivery and several studies have shown that encapsulating drugs to Cyclodextrin polymers decreases adverse side effects of the drugs leading to use lower dosages of drug (Challa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While Chemotherapy has toxic side effects in healthy tissues in treatment of human cancers, Nanotechnology attempts to resolve these problems by encapsulating or loading drugs to nonmaterial which are resistant to drug efflux (Tsuda, 2010;Ghasemali et al, 2013). In recent times, Cyclodextrin nanoparticles are used mostly as recyclable transporters for drug delivery and several studies have shown that encapsulating drugs to Cyclodextrin polymers decreases adverse side effects of the drugs leading to use lower dosages of drug (Challa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…322 Furthermore, this delivery system was designed to actively target cancer cells by binding of transferrin protein ligand on the outer side of the nanoparticle to target transferrin receptors that are highly expressed in cancer cells. 323 Mice bearing subcutaneous Neuro2A tumors were treated by intravenous injection with siRNA-containing nanoparticles. Targeted nanoparticles were significantly more effective in slowing tumor growth than non-targeted nanoparticles given at the same dose.…”
Section: Cyclodextrin Nanoparticlesmentioning
confidence: 99%
“…, China β -caryophyllene β-CD Co-precipitation UV/VIS, DTA, FTIR 6:1 β -Caryophyllene/ β-CD delivery system was able to improve its absorption in rats. (Ghasemali et al, 2013) The inclusion process of CD-tanshinone was a simultaneous and enthalpy-controlled process and it satisfied the law of enthalpy-entropy compensation. The inclusion complex demonstrated was much faster dissolution ratio, increased solubility and decreased in crystallinity.…”
mentioning
confidence: 79%
“…Surprisingly, when in vitro, the antitumoral action of APH-CD was about 2-fold lower than that of the APH free treatment. Others studies employed a cytotoxicity assay, as did Ghasemali et al (2013), who encapsulated a cytotoxic chemotherapeutic agent. They showed that β-CD-helanin complexes inhibited the growth of a T47D breast cancer cell line in a time and dosedependent manner.…”
Section: Pharmacological Improvementmentioning
confidence: 99%